RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PENGGAJIAN DI GANESHA OPERATION CABANG KARAWANG - Hakim, Lukman; Lesmana, Wawan; Ferliyanti, Herlina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Payroll system is the company's operational activities in managing employees. Data processing relating to payroll is very complex because it relates to income tax whose rules often change and other allowances so that the payroll system requires continuous modification. With the making of a payroll system application can facilitate the company in calculating salaries consisting of basic salary, overtime pay, absenteeism and allowances. Information systems can launch a company's economic growth by processing data quickly and precisely can produce accurate reports that are needed by the company in decision making.